# Fight Finance

#### CoursesTagsRandomAllRecentScores

 Scores keithphw $6,001.61 Yuan$1,726.43 Zin $1,619.43 Jade$1,555.80 Carolll $1,522.43 Visitor$1,428.33 Visitor $1,373.33 zy$1,349.70 cuiting $1,289.70 Visitor$1,268.61 Visitor $1,251.28 Visitor$1,249.70 Visitor $1,153.33 Emma Lu$1,100.00 Skywalke... $1,070.00 mm11$1,050.33 ninalee $1,039.70 Visitor$1,035.61 Visitor $1,024.70 Doris$1,009.70

Question 65  annuity with growth, needs refinement

Which of the below formulas gives the present value of an annuity with growth?

Hint: The equation of a perpetuity without growth is: $$V_\text{0, perp without growth} = \frac{C_\text{1}}{r}$$

The formula for the present value of an annuity without growth is derived from the formula for a perpetuity without growth.

The idea is than an annuity with T payments from t=1 to T inclusive is equivalent to a perpetuity starting at t=1 with fixed positive cash flows, plus a perpetuity starting T periods later (t=T+1) with fixed negative cash flows. The positive and negative cash flows after time period T cancel each other out, leaving the positive cash flows between t=1 to T, which is the annuity.

\begin{aligned} V_\text{0, annuity} &= V_\text{0, perp without growth from t=1} - V_\text{0, perp without growth from t=T+1} \\ &= \dfrac{C_\text{1}}{r} - \dfrac{ \left( \dfrac{C_\text{T+1}}{r} \right) }{(1+r)^T} \\ &= \dfrac{C_\text{1}}{r} - \dfrac{ \left( \dfrac{C_\text{1}}{r} \right) }{(1+r)^T} \\ &= \dfrac{C_\text{1}}{r}\left(1 - \dfrac{1}{(1+r)^T}\right) \\ \end{aligned}

The equation of a perpetuity with growth is:

$$V_\text{0, perp with growth} = \dfrac{C_\text{1}}{r-g}$$